Predictors and prognostic impact of silent coronary artery disease in asymptomatic high-risk patients with diabetes mellitus. (1st October 2017) - Zellweger, Michael J.; Haaf, Philip; Maraun, Michael; Osterhues, Hans H.; Keller, Ulrich; Müller-Brand, Jan; Jeger, Raban; Pfister, Otmar; Brinkert, Miriam; Burkard, Thilo; Pfisterer, Matthias; ,
Abstract: Aims: Evaluation of predictors of silent coronary artery disease (SCAD) in high-risk asymptomatic diabetic patients and to evaluate their two-year outcome. Methods and results: Four hundred diabetic patients without prior CAD but at high CAD risk underwent myocardial perfusion scintigraphy (MPS) in this prospective multicentre outcome trial. MPS were abnormal in 22% of patients. Male sex (OR 2.223, 1.152–4.290; p = 0.017), diabetes duration (OR 1.049, 1.015–1.085; p = 0·005), peripheral artery disease (OR 2.134, 1·150–3.961; p = 0.016), smoking (OR 2.064, 1.109–3.839; p = 0·022), systolic blood pressure (OR 1.014, 1.00–1.03, p = 0·056), brain natriuretic peptide (OR 1.002, 1.001–1.004, p = 0·005) independently predicted an abnormal MPS: if < 2 and > 3 predictors were present, 3.2% and 47% patients had an abnormal MPS, respectively (p < 0·001). Two-year major adverse cardiac event rates increased from 2·9% to 14·6%, cardiac death rates from 0·6% to 4·1% in patients with summed stress scores ≤ 10 and > 10%, respectively (each p < 0.045). Conclusions: Male sex, diabetes duration, peripheral artery disease, smoking, elevated systolic blood pressure and increased brain-natriuretic peptides independently predicted SCAD. In presence of > 3 predictors, almost 50% of patients had an abnormal MPS. They may benefit from screening by MPS since the extent of the MPS abnormality discriminated clearly between a favourable compared to a bad 2-year outcome. However, even highest risk patients without objective evidence of CAD had a benign prognosis without need for specific evaluation or therapy. Trial Registration Number: ISRCTN87953632.